Latin America and the Caribean in the transition to a knowledge-based society : an agenda for public policy (ECLAC SantiagoCL, 2000)
Provides a brief description of the main tasks of the rew information and knowledge-based economy. Summarizes some of the built-in characteristics of the social model for the organization of production that has been emerging in most of the Latin American and Caribbean countries in the wake of the structural reforms of the 1990s. Dicusses the characteristics of the information and communications technologies (ICTs) in the region. Explores possible courses of action with a view to helping to ensure that Latin America and the Caribbean will become full-fledged participants in the information and knowledge-based economy and that ICTs are used to promote an equitable form of development that makes provision for the participation of the citizenry.
Bibliography: p. 27